Primary pineal alveolar rhabdomyosarcoma in an adult patient: a case report and literature review - Tao Chang; Chang Ding; Yanhui Liu; Yuan Yang; Qing Mao (BMC Neurology)
Abstract Background The rarity of adult primary cerebral rhabdomyosarcoma (PCRMS) cases has necessitated the adoption of pediatric rhabdomyosarcoma (RMS) therapeutic protocols, highlighting a critical need for expanded treatment experiences to enhance prognoses. Case presentation A 21-year-old female presented to our facility with a 20-day history of persistent headache, nausea, and vomiting, along with mild upward gaze palsy for the past 5 to 7 days. A brain magnetic resonance imaging (MRI) revealed a mass in the pineal region, extending into the third ventricle, measuring approximately 2.5 × 2.0 × 3.0 cm. The lesion exhibited mild irregular lobulation and heterogeneous enhancement. Intraoperatively, it displayed characteristics similar to high-grade gliomas, including a grayish appearance, abundant vasculature, firm texture, and indistinct margins adjacent to the bilateral thalamus. Pathology confirmed alveolar PCRMS with FOXO1 gene rearrangement. Whole-body imaging following pathological diagnosis showed no evidence of skull base infiltration or extracranial metastasis. Despite comprehensive multimodal treatment, including surgery, stereotactic radiotherapy, and chemotherapy, tumor recurrence occurred three months after initial surgery, and the patient unfortunately succumbed to the disease eight months after her initial diagnosis. Conclusions Alveolar PCRMS in the pineal region, a distinct subtype of RMS, is exceptionally rare and typically associated with a bleak prognosis, suggesting unique tumor biology. A multidisciplinary and aggressive management approach is crucial. Further research into the molecular makeup of RMS in adults may pave the way for more effective, tailored treatments for this aggressive disease.